IAEA activities on 67Cu, 186Re, 47Sc Theranostic radionuclides and Radiopharmaceuticals - Jalilian, A. R.; Gizawy, M. A.; Alliot, C.; Takacs, S.; Chakarborty, S.; Rovais, M. R. A.; Pupillo, G.; Nagatsu, K.; Park, J. H.; Khandaker, Mayeen Uddin *; Mikolajczak, R.; Bilewicz, A.; et al. (Bentham Science Publishers, 2020)
Despite interesting properties, the use of 67Cu, 186Re and 47Sc theranostic radionuclides in preclinical studies and clinical trials is curtailed by their limited availability due to a lack of widely established production methods. An IAEA Coordinated Research Project (CRP) was initiated to identify important technical issues related to the production and quality control of these emerging radionuclides and related radiopharmaceuticals, based on the request from IAEA Member States. The international team worked on targetry, separation, quality control and radiopharmaceutical aspects of the radionuclides obtained from research reactors and cyclotrons leading to preparation of a standard recommendations for all Member States. The CRP was initiated in 2016 with fourteen participants from thirteen Member States from four continents. Extraordinary results on the production, quality control and preclinical evaluation of selected radionuclides were reported in this project that was finalized in 2020. The outcomes, outputs and results of this project achieved by participating Member States are described in this minireview.